A severe complication of mid urethral tapes solved by laparoscopic tape removal and ureterocutaneostomy - Schätz, Tobias; Hruby, Stephan; Colleselli, Daniela; Janetschek, Günter; Lusuardi, Lukas (Canadian Urological Association Journal, 2013)
Mid-urethral tapes are largely used to manage stress urinary incontinence(SUI). In certain cases, however, this procedure results in bothersome complications that lead to complete resection. We present the case of an 85-year-old woman who presented with ongoing suprapubic pain, hematuria, vaginal bleeding and recurrent urinary tract infections. The patient had undergone a tension-free vaginal tape (TVT) procedure in 1999 and a transobturator tape (TOT) placement in 2003 for SUI. Investigations revealed a urethral stone, erosion of both TOT and TVT and an urethra-vaginal fistula. Under local anesthesia the urethral stone was removed endoscopically and the TOT removed via a vaginal approach. Due to her comorbidity, she underwent a laparoscopic intraperitoneal removal of the TVT and a definitive ureterocutaneostomy to relieve her pain, inflammation and incontinence. This is the first ever presented case of erosion of mid-urethral tapes and incontinence treated with a laparoscopic resection of the tape and ureterocutaneostomy as definitive urinary diversion.